Jak funkcjonowanie w strefie euro wpływa na stabilizację gospodarczą jej krajów członkowskich? - Mucha-Leszko, Bogumiła (How Does the Functioning of the Euro Area Influence Economic Stabilization of its Members Countries?, 2009)
The purpose of this paper is presenting the newest research results concerning stabilizing impact of the common currency on EMU area economy. In the conclusion, there were underlined the main effects of introducing EMU: 1) accelerating integration of product and financial services markets, 2) accelerating economic convergence processes, 3) improvement in the conditions of developing external balance and monetary policy credibility, 4) changes in capital market vulnerability to domestic shocks and those deriving from the euro (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 1, s. 247-255